Influence of permanent dipole and dynamic core-electron polarization on tunneling ionization of polar molecules - Hoang, Van-Hung; Zhao, Song-Feng; Le, V. H.; Le, Anh Thu (My University, 2017)
We present a detailed theoretical investigation on strong-field ionization of polar (CO and NO) as well as nonpolar molecules (N-2, O-2, and CO2). Our results indicate that accounting for the Stark correction in the molecular tunneling ionization theory leads to overall fairly good agreements with numerical solutions of the time-dependent Schrodinger equation. Furthermore, we show that the effect of dynamic core-electron polarization, in general, has a weak influence on the angle-dependent ionization probability. However, in the case of CO we confirm the recent finding by B. Zhang, J. Yuan, and Z. Zhao [Phys. Rev. Lett. 111, 163001 (2013)] that accounting for dynamic core-polarization is crucial to achieving an overall good agreement with experiments.
Citation: Hoang, V. H., Zhao, S. F., Le, V. H., & Le, A. T. (2017). Influence of permanent dipole and dynamic core-electron polarization on tunneling ionization of polar molecules. Physical Review A, 95(2), 8. doi:10.1103/PhysRevA.95.023407
Keywords: High-Harmonic Interferometry; Field; Diffraction; Atoms; Wave; Optics